Desorption Regeneration Performance of Magnetic Bentonite after Pb(II) Adsorbed. Issue 4 (25th January 2019) - Zou, Chenglong; Jiang, Wei; Liang, Jiyan; Guan, Yinyan; Sun, Xiaohang
Abstract: Bentonite and its modifications have been widely used in the environmental pollution control and adsorption of heavy metals ions due to the large surface area, high adsorption capacity and low cost. However, it will become hazardous solid waste after saturation adsorption with a difficult problem to treat it. So the saturated adsorbent after adsorption of heavy metal ions needs to be disposed of properly. It will be of great scientific and economic value to study the regeneration recycling of bentonite after heavy metals ions adsorption. Desorption regeneration of magnetic bentonite (M−B) after Pb(II) adsorption with NaNO3 solution was studied in this paper. The effects of several parameters on desorption regeneration were explored and it showed effective desorption regeneration performance. The desorption rate reached 90.21% using 50 mL g –1 and 1.00 mol L –1 NaNO3 desorption liquid at pH 3.0, 35 °C for the first time.The desorption process better conformed to the second‐order kinetic equation and the Langmuir model. The physical and chemical feature of regenerated M−B and the original were comparatively analyzed by XRD, FT‐IR, SEM and BET. It showed that M−B still remained stable structure after 6 times adsorption–desorption cycles. The study will provide useful experiences and references for its high effective utilization. Abstract : The desorption regeneration of magnetic bentonite (M−B) after Pb(II) adsorbed and reuse for Pb(II) adsorption were studied in this paper. The results showed stable performance on the adsorption and desorption regeneration during 6 times cycles and still maintained stable physical and chemical structures.